A alquimia da palavra: Fernando Pessoa e as ciências ocultas - Oliveira, Anderson Amaral de (2011)
Fernando Pessoa has changed his country s culture driving his nation to a vanguard position on modern culture. He abdicated enjoying life to transform it into his work, built up considering the author s deep knowledge in theories of occult sciences, making alchemy and occultism an important authorial strategy, transforming his knowledge to an esthetic resource for his work, from the very first until the last poem as the biggest alchemic work ever seen in a literature. Such realization maybe doesn t have the same effects for the occult sciences, however its symbolic, metaphoric and analogical power depurate the literature, at the same time, it looks towards to sublimate the poet s life through his work.